2016
DOI: 10.17795/jjcdc-33229
|View full text |Cite
|
Sign up to set email alerts
|

Study of Risk Factors for Esophageal Cancer in Khorramabad City From 2012 - 2014

Abstract: Background: Esophageal cancer is of major concern worldwide, ranking sixth as the most common cause of cancer mortality. Lifestyles such as cigarette smoking, alcohol consumption, and poor dietary habits have been suggested to be associated with the carcinogenesis of esophageal cancer. Objectives: This study aimed to determine the factors affecting and associated with esophageal cancer in Khorramabad city from 2012 to 2014. Patients and Methods: This is an analytical study of 48 patients with esophageal cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…14 In another case control study, Moradi and colleagues found that 21.6% of cases but no one in the control group had EC in their first degree relatives (OR=7.6, p =0.001). 15 Since the role of family history have genetic and environmental elements in the pathogenesis of EC, more studies should be considered. …”
Section: Introductionmentioning
confidence: 99%
“…14 In another case control study, Moradi and colleagues found that 21.6% of cases but no one in the control group had EC in their first degree relatives (OR=7.6, p =0.001). 15 Since the role of family history have genetic and environmental elements in the pathogenesis of EC, more studies should be considered. …”
Section: Introductionmentioning
confidence: 99%